People’s Talents, People’s Welfare: Educational Economics since 1965 - Jozef M. M. Ritzen, (Communication Today, 2025)
In the past fifty years our knowledge of talent development in the schools has vastly improved, putting the quality of the teacher center stage. Gradually we are also improving our understanding of the contribution of education to talents in the form of character skills. Less well researched is the impact of the organizational form of the delivery of education on learning, although some steps have been made in understanding the importance of the empowerment of teachers. The demands for skills have, in the meantime, shifted towards non-routine work, while character skills have become more important. At the same time, the wage distribution has become more unequal and is likely to remain so in the near future. The education system has been slow to take this external world on board because education policy is often too partisan, too party-political to provide a stable structure for change. Funding of education and equality of opportunity have not been advanced as they should because of social myopia: other sectors or social goals with an immediate impact on citizens are prioritized in the political process, while education is an investment which only pays off after a long time.